Do Anxiety and Depression Predict Persistent Physical Symptoms After a Severe COVID-19 Episode? A Prospective Study - Bottemanne, Hugo; Gouraud, Clément; Hulot, Jean-Sébastien; Blanchard, Anne; Ranque, Brigitte; Lahlou-Laforêt, Khadija; Limosin, Frédéric; Günther, Sven; Lebeaux, David; Lemogne, Cédric (Frontiers in Psychiatry, 2021)
Background Persistent physical symptoms are common after a COVID-19 episode, but their pathophysiological mechanisms remain poorly understood. In this study, we aimed to explore the association between anxiety and depression at one-month after acute infection and the presence of fatigue, dyspnea and pain complaints at three-month follow-up. Methods We conducted a prospective study in patients previously hospitalized for COVID-19 followed up for three months. The Hospital Anxiety and Depression Scale (HAD-S) was administered by physicians at one-month follow-up, and the presence of fatigue, dyspnea and pain complaints was assessed at both one month and three months. Multivariable logistic regression explored the association between anxiety and depression subscores and the persistence of each of the physical symptom at three months. Results A total of 84 patients were included in this study (Median age: 60 years, interquartile range: 50.5-67.5 years, 23 women). We did not find any significant interaction between anxiety and the presence of fatigue, dyspnea, or pain complaints at one month in predicting the persistence of these symptoms at three months (all p≥0.36). In contrast, depression significantly interact with the presence of pain at one month in predicting the persistence of pain at three months (OR: 1.60, 95% CI: 1.02-2.51, p=0.039), with a similar trend for dyspnea (OR: 1.51, 95% CI: 0.99-2.28, p=0.052). Discussion & Conclusion Contrary to anxiety, depression after an acute COVID-19 episode may be associated with and increased risk of some persistent physical symptoms, including pain and dyspnea.